"… And Please Visit Our Facebook Page, Too!" How Radio Presenter Personalities Influence Listeners' Interactions With Radio Stations. Issue 1 (2nd January 2016) - Spangardt, Benedikt; Ruth, Nicolas; Schramm, Holger
Abstract : Radio personalities or presenters are important to music radio stations, as their individual personalities influence if, how, and to what extent listeners want to interact with radio stations and presenters during programs. Both parasocial interaction with the presenter and flow experiences are believed to mediate the listener–presenter relationship. With this in mind, we conducted an experiment in which 236 German radio listeners aged 14 to 49 were asked to listen to the same radio show, but with varying presenters. Mediation analysis revealed notable effects of presenters' personalities on listeners' behavioral intentions. Both parasocial interaction and flow were found to be important mediators of the discovered effects.